Aplikasi Multimedia sebagai Media Pembelajaran Sejarah Indonesia Masa Perjuangan Kemerdekaan Untuk Sekolah Dasar Berbasis Android - Aulia Nastiti; R. Rizal Isnanto; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2015)
History teaching at school needs new methods to improve students' interest in learning history. This is because method that commonly used in schools is where students only listen to what teacher explained. The textbooks used usually only have few illustrations so that students are less interested and easily bored. Based on this problem, A Multimedia Learning Application was built and it is specifically made for Android devices. This application is expected to support the learning process at school. It was built using the Unity Engine. Adobe Illustrator and Adobe Photohop also used to create application's design and illustrations to improve application's interface. Development method used for this application is the Multimedia Development Life Cycle (MDLC). This application was tested using the Black Box Test and the Beta Test. Results from Black Box testing is that all functions in this application has been running properly. Results obtained from Beta testing is that more than 75% of respondents gave positive responses to the application and it can be concluded that Multimedia Learning Application can be used to support the learning process at school.